Peran sumber daya manusia dalam manajemen lembaga pendidikan non-formal - Ramdanil Mubarok; Mardiyah Mardiyah; Selvi Devi Rahayu (IKIP Siliwangi Bandung, 2024)
The aim of this research is to analyze the role of human resources, the management process of non-formal educational institutions, and the obstacles to their management. The method used is a qualitative research method with a descriptive type. This research was conducted at the North Sangatta Kasih Bapa Foundation. This research instrument consisted of eight people. The research results show that the management of non-formal education institutions is carried out through planning, organizing, implementing, and evaluating. The management of non-formal educational institutions at the Kasih Bapa Foundation has been running well, although there are differences in the implementation process with other institutions. This does not reduce the impact resulting from the program implementation process. Meanwhile, the role of human resources in non-formal educational institutions is carried out through the process of designing, improving, managing, recruiting, and motivating human resources. The obstacles to managing non-formal educational institutions include teaching staff and parents of students. It is hoped that with a better understanding of the role of human resources, we can identify challenges, opportunities, and strategies that can be implemented to increase the contribution of non-formal education institutions to education and the development of society as a whole.